Práce českých dialektologů včera, dnes a zítra - Ireinová, Martina; Konečná, Hana (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2012)
Koncem roku 2011 vyšel šestý svazek Českého jazykového atlasu – Dodatky. Pět dílů Českého jazykového atlasu bylo vydáno v letech 1992–2005. Připravovali je pracovníci pražského a brněnského dialektologického oddělení Ústavu pro jazyk český AV ČR. Atlas podává všestranný a prohloubený pohled na územní rozrůznění českých nářečí a běžné mluvy, postihuje hlavní tendence jejich vývoje a představuje tak významný soubor údajů ke studiu českého národního jazyka. V současnosti se připravuje jeho elektronická podoba. Materiál nashromážděný výzkumem pro ČJA bude jedním ze zdrojů pro vznikající Slovník nářečí českého jazyka.

At the end of 2011, the sixth volume of the Czech Linguistic Atlas – Supplements appeared. Five volumes of the Czech Linguistic Atlas were published between 1992–2005. It was created by the workers of the Departments of Dialectology of the Institute of the Czech Language in Prague and Brno. The Atlas gives a comprehensive and in-depth view of the territorial diversity of Czech dialects and of common speech, covers the main tendencies of their development and in this way it represents an important set of data for the study of the Czech national language. Currently, its electronic version is being prepared. The material collected for the Czech Linguistic Atlas will be one of the sources for the future Dictionary of Czech dialects.
Work of the Czech dialectologists yesterday, today, and tomorrow
Keywords: Lingvistika; Linguistic; Dialektologie; Dialectology; Česká nářečí; Czech dialects; Český jazykový atlas; Czech Linguistic Atlas